Vigorous Intervals and Hypoglycemia in Type 1 Diabetes: A Randomized Cross Over Trial. Issue 1 (December 2018) - Rempel, Meaghan; Yardley, Jane; MacIntosh, Andrea; Hay, Jacqueline; Bouchard, Danielle; Cornish, Stephen; Marks, Seth; Hai, Yan; Gordon, Joseph; McGavock, Jonathan
Abstract Adding vigorous-intensity intervals (VII) to moderate-intensity exercise prevents immediate declines in blood glucose in type 1 diabetes (T1D) however the intensity required to minimize post-exercise hypoglycemia is unknown. To examine this question, ten sedentary T1D individuals completed four treadmill exercise sessions: a control session of 45 minutes of walking at 45–55% of heart rate reserve (HRR) and three sessions consisting of 60 seconds (VII) at 70%, 80%, or 90% of HRR every 4 minutes during exercise at 45–55% of HRR. We used continuous glucose monitoring (CGM) to measure time ≤3.9 mmol/L, glucose variability, hypoglycemia frequency and area under the curve (AUC) for hypoglycemia and hyperglycemia for 12 hours post-exercise. We also examined growth hormone and cortisol responses during and following exercise. In the 12 hours post-exercise, the percentage of time ≤3.9 mmol/L, glucose variability, and AUC for hypoglycemia and hyperglycemia were similar across conditions. The frequency of hypoglycemic events was highest after the 90% intervals compared to the control arm (12 vs 3 events, p = 0.03). There was a trend towards elevated growth hormone with increasing exercise intensity but cortisol levels were similar across conditions. Adding VII to moderate intensity exercise may increase hypoglycemia risk at higher intensities.